Quality of life in older adults and sports practice motives - Ibáñez Pérez, Ricardo José; Martínez-Moreno, Alfonso; Cavas-García, Francisco; Cano-Noguera, Francisco (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Regular physical activity practice provides benefits and improves quality of life (QOL). The purpose of this study was to know the level of QOL of older adults who practice physical activity. The study was quantitative, descriptive and cross-cutting with accidental sampling, with 554 participants of which 37.2% (n=206) are men and 62.8% (n=348) women, with an average age of around 65 years (M=64.9; DT=10.3). To know the QOL of the sample members, the WHOQOL-BREF questionnaire was used, 26 items and four dimensions, with five-option Likert scale responses (1-5). Regarding statistics, Cronbach alpha, Pearson linear correlation, t-Student, ANOVA, Kolmogorov-Smirnov and Levene test were applied with SPSS 25.0 for Windows. Regarding the results, it should be noted that the environment dimension was the best valued followed closely by the psychological health dimension and the worst valued was social relationships. There were no significant differences in sex. In terms of age, when one gets older, psychological health and the environment decrease, while increasing social relationships. In conclusion, older adults with academic qualifications had better values in psychological health and in the environment.